Development of universal LED driver for low power application - Abbasi, I. (Institute of Electrical and Electronics Engineers Inc., 2014)
In this work, a universal LED driver is designed based on microcontroller which has the main function to drive different current levels for LEDs power up. Pulse width modulation is applied to vary the output current. Two power LEDs with current rating of 350 mA and 700 mA respectively have been selected as loads and a microcontroller, ATmega328 is programmed through Arduino UNO. Proposed design is simulated and a prototype is fabricated for verification. Both simulation and experimental works have shown good relationship in results justification. Hence this indicates potential development for a large scaled universal LED drivers. Â© 2014 IEEE.